Successful Treatment of Severe Hemolytic Disease of the Newborn Caused by Anti-Jkb - Goo Lyeon Kim; Yoonsoo Kim; Young Pyo Chang; Ju-Hee Seo; Mee Jeong Lee (The Korean Society of Pediatric Hematology-Oncology, 2021)
Hemolytic disease of the newborn (HDN) is a condition in which maternal antibodies cross the placenta and cause hemolytic reactions. Anti-RhD was the most common cause, but with the introduction of immunoglobulin, the frequency has decreased significantly, making hemolytic disease caused by other minor blood g roups more important. Kidd antigen is also known to cause hemolytic transfusion reactions. Only 13 cases have been reported so far, because Kidd antigen dose not usually cause HDN. Most cases have a good outcome, and only two fatal cases have been reported. A four-day-old male patient was hospitalized for jaundice, and hemolysis was confirmed by blood test. The mother's blood was Jkb antibody positive. The patient did not improve with phototherapy, so an exchange transfusion was performed. Additional hemolysis occurred, so we undertook transfusion of red blood cells, resulting in cessation of hemolysis. We report HDN caused by Jkb antibody that responded to exchange blood transfusion.